Characteristics and influencing factors of organic fouling in forward osmosis operation for wastewater applications: A comprehensive review. (August 2019) - Ly, Quang Viet; Hu, Yunxia; Li, Jianxin; Cho, Jinwoo; Hur, Jin
Abstract: Wastewater reuse is considered one of the most promising practices for the achievement of sustainable water management on a global scale. In the context of the safe reuse of water, membrane filtration is a competitive technique due to its superior efficiency in several processes. However, membrane fouling by organics is an inevitable challenge that is encountered during the practical application of membrane processes. The resolution of the membrane fouling challenge requires an in-depth understanding of many complex interactions between organic foulants and the membrane. In the last few decades, the forward osmosis (FO) membrane process, which exploits osmosis as a driving force, has emerged as an effective technology for water production with low energy consumption, thus leveraging the water-energy nexus. However, their successful application is severely hampered by membrane fouling, which is caused by such complex fouling mechanisms as cake enhanced osmotic pressure (CEOP), reverse salt diffusion (RSD), internal, and external concentration polarization as well as by the traditional fouling processes encompassing colloids, microbial (biofouling), inorganic, and organic fouling. Of these fouling types, the fouling potential of organic matter in FO has not been given sufficient attention, in particular, when FO is applied to wastewater treatment. This paper aims to provide a comprehensive overview of FO membrane fouling for wastewater applications with a special focus on the identification of the major factors that lead to the unique properties of organic fouling in this filtration process. Based on the critical assessment of organic fouling formation and the governing mechanisms, proposals were advanced for future research aimed at the mitigation of FO membrane fouling to enhance process efficiency in wastewater applications. Highlights: A first review to compare various factors influencing FO membrane fouling Characterizing tools for FO membrane foulants are summarized. Unique properties of foulant layer in FO were compared with those of RO. Many factors for FO membrane fouling are identified and compared individually.